An Integrative Literature Review on English Teachers as Agents of Change - Lina Betancurt; Liliana del Pilar Gallego (Profile Issues in Teachers' Professional Development)
In this article, we attempt to understand English teachers’ perceptions, practices, and challenges concerning social agency through an integrative literature review to build and draw an interpretative framework and generate new knowledge. To achieve this, 58 empirical studies published in a period of seventeen years—2006 to 2023—were selected from the Scopus and Web of Science databases. Results showed that English language teachers’ perceptions of agency were closely related to structural factors. Practices such as interactions with communities and humanistic approaches can make agency meaningful. Challenges in agency were more related to collective agency and reflections. In conclusion, English teachers’ agentic actions are not dampened by structural factors; on the contrary, this review confirms the potential of English educators to transform education.